Pengembangan Instrumen Angket Faktor-Faktor Penyebab Kesulitan Belajar Siswa pada Materi Asam Basa Kelas XI Fase F SMA - Nala Sarita; Bali Yana Fitri (Lembaga Yasin AlSys, 2026)
Chemistry learning difficulties are a problem frequently experienced by students because chemistry material requires conceptual understanding and the ability to connect macroscopic, microscopic, and symbolic representations. This condition is influenced by various internal and external factors, making a valid and reliable questionnaire instrument necessary to accurately identify the factors causing learning difficulties. This study aims to develop a valid and reliable questionnaire instrument on the factors causing students’ learning difficulties in acid-base material. This study used the Research and Development method by adapting the eight steps of scale development according to DeVellis, including construct determination, item statement development, measurement format determination, content validation, instrument revision, empirical testing, item evaluation, and scale length determination. The content validity of the instrument was assessed by five chemistry education expert lecturers using Aiken’s V index, while empirical validity was analyzed using Pearson Product Moment correlation and reliability using the Cronbach’s Alpha coefficient. The empirical trial involved 125 Grade XI Phase F senior high school students. The results show that the instrument had an average Aiken’s V value of 0.89, which falls into the valid category. The empirical validity test results show that all 25 statement items met the validity criteria, with calculated r values ranging from 0.289 to 0.678 and greater than the r table value of 0.1743. In addition, the instrument obtained a Cronbach’s Alpha value of 0.86, indicating very high reliability. The conclusion of this study affirms that the developed questionnaire instrument is valid, reliable, and feasible for use in identifying the factors causing students’ learning difficulties in acid-base material. The implications of this study provide practical contributions for chemistry teachers in conducting early diagnoses of learning difficulties and supporting the development of learning strategies that are more aligned with students’ needs.